English Teachers’ Perception toward the Switch from Offline to Online Teaching during lockdown in the Midst of Covid-19 Outbreak - Muhammad Nashir; Roudlotun Nurul Laili (Universitas Pahlawan Tuanku Tambusai, 2021)
Education is one of the sectors that is badly influenced by covid-19 pandemic where the learning process is carried out from home. This sudden pandemic requires teachers to switch from face-to-face learning into learning domain with technological network. The objective of this study was to describe English teachers’ perception toward the switch from offline to online teaching during lockdown in the midst of covid19 outbreak. The subject of study was 50 English teachers of Senior High School in Banyuwangi. The research method was case study with qualitative research approach. The data needed collected by distributing Google form questionnaire and interview. The result of study indicated that English teachers’ perception about online teaching have not been performed properly, they stated that only for about 35% students who were active and really serious in carrying out online learning and collecting the assignments given on time because of lacking flexibility and access from teachers in controlling students’ learning activities. 68% teachers felt that their workload was heavier if compared to face-to-face learning because they need additional time to operate appropriate online learning media and package interesting learning in order to be able to increase students’ motivation and desire in English lesson.